Learning with William Stern : personology for future - Fircks, Enno von (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"William Stern was an important German psychologist. What remains rather preserved from his scientific heritage is centered around the notion of intelligence and differential psychology. Yet, Stern's scientific work is more complex than that. For instance, William Stern has laid the groundwork for a philosophical system - called critical personology - being a groundwork for the psychological sciences in general. This book tries to restore and expand Stern's philosophical ideas of critical personology while showing pathways how to apply this expansion to applied fields of psychology such as career counselling, psychological mediation, psychotherapy, personnel selection among many other domains of psychology. With the present book, critical personology can become a theoretical, methodological and interventional tool with which psychologists of various disciplines might work in their related fields. As such, the book will be rewarding for multiple audiences. First, scholars of the history of psychology might use the insights of the book in order to acknowledge Stern's forgotten theories such as about Stern's notion of the unconscious. Second, psychologists being interested in a wholistic approach towards psychology will gain useful knowledge and tools how to better understand the complexity and dynamic of the person (especially the person's needs, drives, motives and so forth). Third, applied psychologists can use the various frameworks in order to diversify their methodological and interventional knowledge and help people to better understand themselves as well as to adjust to their environments"-- Provided by publisher.
Keywords: Stern, William, -- 1871-1938.; Psychology -- Germany -- History.; Personality.; Psychology -- Personality.; Psychological theory, systems, schools and viewpoints.; Psychology: the self, ego, identity, personality.; elektronické knihy; electronic books